Exon deletions of SPG4 are a frequent cause of hereditary spastic paraplegia. Issue 4 (10th November 2006) - Depienne, Christel; Fedirko, Estelle; Forlani, Sylvie; Cazeneuve, Cécile; Ribaï, Pascale; Feki, Imed; Tallaksen, Chantal; Nguyen, Karine; Stankoff, Bruno; Ruberg, Merle; Stevanin, Giovanni; Durr, Alexandra; et al.
Abstract : Background: Point mutations in SPG4, the gene encoding spastin, are a frequent cause of autosomal dominant hereditary spastic paraplegia (AD-HSP). However, standard methods for genetic analyses fail to detect exonic microdeletions. Methods: 121 mutation-negative probands were screened for rearrangements in SPG4 by multiplex ligation-dependent probe amplification. Results: 24 patients with 16 different heterozygotic exon deletions in SPG4 (20%) were identified, ranging from one exon to the whole coding sequence. Comparison with 78 patients with point mutations showed a similar clinical picture but an earlier age at onset. Conclusions: Exon deletions in SPG4 are as frequent as point mutations, and SPG4 is responsible for 40% of AD-HSP.